AtCIPK16, a CBL-interacting protein kinase gene, confers salinity tolerance in transgenic wheat - Imtiaz, Khadija; Ahmed, Moddassir; Annum, Nazish; Tester, Mark; Saeed, Nasir A. (Frontiers in Plant Science, 2023)
Globally, wheat is the major source of staple food, protein, and basic calories for most of the human population. Strategies must be adopted for sustainable wheat crop production to fill the ever-increasing food demand. Salinity is one of the major abiotic stresses involved in plant growth retardation and grain yield reduction. In plants, Calcineurin-B-like proteins form a complicated network with the target kinase CIPKs (CBL-interacting protein kinases) in response to intracellular calcium signaling as a consequence of abiotic stresses. AtCIPK16 gene has been identified in Arabidopsis thaliana and found to be significantly upregulated under salinity stress. In this study, the AtCIPK16 gene was cloned in two different plant expression vectors i.e., pTOOL37 having UBI1 promoter and pMDC32 having 2XCaMV35S constitutive promoters transformed through Agrobacterium-mediated transformation protocol, in local wheat cultivar Faisalabad-2008. Based on their ability to tolerate different levels of salt stress (0 mM, 50 mM, 100 mM, and 200 mM), transgenic wheat lines OE 1, 2, 3 expressing AtCIPK16 under UBI1- promoter and OE 5, 6, 7 expressing the same gene under 2XCaMV35S promoter were performed better at 100 mM salinity stress as compared to wild type. AtCIPK16 overexpressing transgenic wheat lines were further investigated for their ability of K+ retention in root tissues by utilizing Microelectrode Ion Flux Estimation technique. It has been demonstrated that after 10 min of 100 mM NaCl application, more K+ ions retained in AtCIPK16 over expressing transgenic wheat lines as compared to wild type. Moreover, it could be concluded that AtCIPK16 functions as positive elicitor in sequestering Na+ ions into the cell vacuole and retaining more cellular K+ under salt stress to maintain ionic homeostasis.